Assessment of pre and post Neonatal Resuscitation program (NRP) training in a neonatal intensive care unit of Pakistan - Fatima, Kaneez; Zulfiqar, Sughra; Naseer, Nauman; Shabbir, Saima; Bano, Tasleem (Journal of University Medical & Dental College, 2024)
ABSTRACT Background & Objective: Approximately 300,000 newborns arrive daily, but 5-10% require resuscitation, and 1-10% need ventilation. Globally, 4 million infants die within four weeks due to inadequate healthcare resources and training. Neonatal Resuscitation Programs (NRP) aim to reduce infant mortality by training healthcare professionals in essential skills for newborn resuscitation. Methodology: In this comparative descriptive study, we aimed to assess the efficacy of the Neonatal Resuscitation Program (NRP) training conducted at the Neonatal Unit of CMH Hospital in Rawalpindi on December 20, 2022. We selected a cohort of 111 participants, including healthcare professionals like physicians, specialists, nurses, and others, regardless of age or gender, through non-probability purposive sampling. The training spanned eight hours, equipping participants with vital skills and Knowledge in neonatal resuscitation. We administered pre-training and post-training questionnaires to gauge their proficiency and comprehension of neonatal resuscitation protocols. Responses were collected, documented, and statistically analyzed using SPSS v-26. Results: The study population demonstrated a mean pre-training score of 61.72±19.65%, significantly increasing to 85.8±10.9% after completing the NRP training (p<0.0001). These results indicate the remarkable success of the Neonatal Resuscitation Program in enhancing the Knowledge and skills of healthcare professionals engaged in neonatal care, thereby contributing to improved patient outcomes. Conclusion: The Neonatal Resuscitation Program (NRP) proved highly impactful in refining the aptitudes and proficiency of healthcare professionals involved in neonatal care. These findings highlight the importance of such training programs in reducing neonatal mortality rates and enhancing the quality of care provided to newborns.